2012
DOI: 10.1109/tap.2011.2167907
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Directional Logging Tools in Anisotropic and Multieccentric Cylindrically-Layered Earth Formations

Abstract: Abstract-We develop a pseudoanalytical method for the analysis of directional resistivity well-logging tools consisting of multiple tilted-coil antennas in cylindrically-layered Earth formations which have anisotropic conductivities and where each layer may be eccentric to the others (multieccentric formations). The cylindrically-layered, anisotropic, and multieccentric scenarios considered here are often encountered in deviated/horizontal drilling for hydrocarbon exploration, where the logging tool may be ecc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…In the radial direction, each region is modeled as a bounded, radially-stratified waveguide. Field solutions for Maxwell's equations in uniaxially anisotropic multilayered cylindrical structures are well-known, and to avoid repetition, we adopt here a notation similar to that in [6,8,15,47,48,50] by assuming a time-harmonic dependence in the form exp(−iωt). It should be observed that the notation adopted here despite being very similar to that in [48] and [15], differs slightly in a few places.…”
Section: Electromagnetic Fields In Cylindrical Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…In the radial direction, each region is modeled as a bounded, radially-stratified waveguide. Field solutions for Maxwell's equations in uniaxially anisotropic multilayered cylindrical structures are well-known, and to avoid repetition, we adopt here a notation similar to that in [6,8,15,47,48,50] by assuming a time-harmonic dependence in the form exp(−iωt). It should be observed that the notation adopted here despite being very similar to that in [48] and [15], differs slightly in a few places.…”
Section: Electromagnetic Fields In Cylindrical Structuresmentioning
confidence: 99%
“…Over the years, various techniques have been used to properly model logging-while-drilling (LWD) tools used in hydrocarbon exploration [8,14,15,26,47,48]. The complex geophysical formations that are prevalent in this type of problem can be handled using brute-force numerical techniques such as finitedifferences (FDs), finite-elements (FEs) and finite-volumes (FVs) [6,7,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is still impractical to employ brute-force methods in inversion efforts where a large number of forwards simulation is required for a parameter space sweep. On the other hand, methods that combine both numerical and analytical steps [8][9][10][11][12][13], such as the numerical mode-matching (NMM) [14][15][16][17], are able to model complex geophysical formations while requiring only a modest amount of computational resources compared to brute-force methods.…”
Section: Introductionmentioning
confidence: 99%